Biomass loss and change in species dominance shift stream community excretion stoichiometry during severe drought. (2nd December 2019) - Hopper, Garrett W.; Gido, Keith B.; Pennock, Casey A.; Hedden, Skyler C.; Guinnip, James P.; Fisher, Molly A.; Tobler, Courtney M.; Hedden, Crosby K.; Bruckerhoff, Lindsey A.
Abstract: Animals contribute significantly to nutrient cycling through excretion, but most studies consider their effects under relatively benign abiotic conditions. Disturbances such as drought may alter animals' nutrient contributions through shifts in species composition and biomass. Headwater streams are particularly vulnerable to extreme climate events and thus might show rapid changes in stream biota and their ecosystem effects. We tested how biomass and subsequent ecosystem effects (nutrient cycling) of an intermittent prairie stream community changed during a drought. We quantified the biomass and contributions to nutrient cycling for assemblages comprising fishes, crayfish, and tadpoles in 12 isolated pools over 3 months encompassing the harshest drought on record for Kings Creek, KS, U.S.A. We predicted that macroconsumer biomass would decline with pool surface area and that differences in macroconsumer biomass and taxonomic composition would lead to different contributions of pool assemblages to nutrient cycling. The biomass of pool assemblages declined with decreasing pool size, a pattern apparently driven by mortality, emigration, or metamorphosis. We also observed a change in assemblage structure of drying pools during drought relative to pool size, shifting dominance toward species with more drought‐resistant traits. Accordingly, assemblage nitrogen (N) excretion rates declined as pool biomass was reduced, leading to a 58% reduction in N available to epilithic biofilms. Phosphorus (P) excretion rates declined from June to July, but increased in August, as species with high P excretion rates maintained similar proportional biomass and biomass of a non‐native fish increased. Molar N:P of pool assemblage excretion declined significantly throughout the drought and coincided with loss of southern redbelly dace ( Chrosomus erythrogaster : Cyprinidae). Animal‐mediated nutrient cycling was altered by the loss of biomass and stoichiometric traits of taxa that differed in their occurrences and ability to tolerate abiotic conditions during drought. Elevated availability of dissolved N in isolated pools may increase N uptake rates by biofilms during drought conditions, indicating the importance of N excreted by aggregated macroconsumers, especially those with unique stoichiometric traits. While the significance of shifts in the composition of freshwater communities to ecosystems is not entirely known, additional losses in ecosystem function and changes in community structure may follow episodes of severe drought.